Efficiency evaluation of sewage treatment technologies: implications on aquatic ecosystem health - Umara Qayoom (IWA Publishing, 2021)
This research paper tries to identify and address issues related to efficiency of sewage treatment plants (STPs) and their implications on the Dal Lake ecosystem in Srinagar city, Kashmir, India. Fluidized aerobic bioreactor (FAB) and sequential batch reactor (SBR) technologies having been recently installed along the periphery of Dal Lake were evaluated for efficiency for a continuous period of 24 months from December 2016 to November 2018. Apart from chemical quality, total coliform (TC), fecal coliform (FC), and fecal streptococci (FS) analyses were also carried out. Major highlights of our work using one-way ANOVA (analysis of variance) revealed significant variations (p < 0.05) in total suspended solids (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonia (NH3-N), total phosphorus (TP), TC, FC, and FS. Our findings indicate that both technologies are struggling for removal efficiency, which is very low, especially in FAB during three to four months of winter season where a very high drop in the working efficiency of the STP was observed. The treatment facilities did not meet the prescribed standards in respect of TSS, BOD, NH3-N, TP, TC, FC, and FS thereby having the potential to compromise public health and trophic status of Dal Lake.